2008
DOI: 10.1002/abc.265
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Intentionally Fostering Student Learning

Abstract: Recognizing the mismatch between a philosophy of holistic development and evaluation focused on external, quantitative criteria led Miami University's Honors and Scholars Program to revise its curriculum in accordance with student development theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Several national studies have identified educational experiences that are associated with enhancing students’ learning and development (AAC&U, 2002, 2007; Association for American Higher Education [AAHE], 1998; Chickering & Gamson, 1991; King, Magolda, Barber, Brown, & Lindsay, 2009; Kuh, Kinzie, Schuh, & Whitt, 2005; Swaner & Brownell, 2008; Taylor & Haynes, 2008). The current study identified 12 educational experiences and placed them within three broad groupings: curricular, cocurricular, and community.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several national studies have identified educational experiences that are associated with enhancing students’ learning and development (AAC&U, 2002, 2007; Association for American Higher Education [AAHE], 1998; Chickering & Gamson, 1991; King, Magolda, Barber, Brown, & Lindsay, 2009; Kuh, Kinzie, Schuh, & Whitt, 2005; Swaner & Brownell, 2008; Taylor & Haynes, 2008). The current study identified 12 educational experiences and placed them within three broad groupings: curricular, cocurricular, and community.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several recent publications have examined factors affecting self‐authorship and have explored ways of organizing educational practices to enhance these capacities (e.g., Baxter Magolda, Creamer, & Meszaros, in press; Bekken & Marie, 2007; Creamer & Laughlin, 2005; Meszaros, 2007; Pizzolato, 2003, 2004, 2005; Taylor, 2008; Taylor & Haynes, 2008). The most detailed descriptions of such practices are found in Baxter Magolda and King's (2004) volume on learning partnerships.…”
mentioning
confidence: 99%
“…The Ohio University Patton College of Education chose to initiate an HP because such programs represent one way that colleges (and secondary schools) address the needs of academically talented students (Berger, 2007;Campbell & Fuqua, 2008;Hébert & McBee, 2007;Long, 2002;Seifert, Pascarella, Colangelo, & Assouline, 2007; K. Taylor & Haynes, 2008). Evidence suggests these programs contribute to positive student outcomes in terms of achievement, social development, and career preparation (e.g., Hébert & McBee, 2007;Ory & Braskamp, 1988;Reed, 1988;Rinn, 2007;Seifert et al, 2007).…”
mentioning
confidence: 99%
“…The Ohio University Patton College of Education chose to initiate an HP because such programs represent one way that colleges (and secondary schools) address the needs of academically talented students (Berger, 2007; Campbell & Fuqua, 2008; Hébert & McBee, 2007; Long, 2002; Seifert, Pascarella, Colangelo, & Assouline, 2007; K. Taylor & Haynes, 2008).…”
mentioning
confidence: 99%